Transformasi Layanan Administrasi Kependudukan Melalui E-Government: Studi Kasus Sobat Dukcapil Kota Tangerang: - - Salsabila, Adinda (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
The transformation of population administration services is a strategic step in improving the quality of public services in the digital era. Before the implementation of e-government, population administration services in Tangerang City faced various challenges, such as slow service processes, complicated bureaucracy, and limited public access to services. This study aims to analyze the transformation process of population administration services through the implementation of e-government, using the Sobat Dukcapil service in Tangerang City as a case study. The research method employed is descriptive qualitative, with data collected through questionnaires distributed to community members who have used the Sobat Dukcapil service. The results indicate that digitalization of services through Sobat Dukcapil has improved efficiency, transparency, and accountability, as well as accelerated the processing of population documents. However, challenges remain, such as the digital literacy gap among the community and limitations in technological infrastructure. Efforts to enhance digital literacy and strengthen infrastructure are key to sustaining this transformation. The study recommends development of service features, enhancement of human resource capacity, and continuous socialization to support the optimal implementation of e-government in the field of population administration. Furthermore, it is important to involve the community in this transformation process so that they can understand and utilize the available services. Thus, population administration services are expected to be more responsive to community needs and contribute to improving the overall quality of life for the residents of Tangerang City. This transformation will not only accelerate administrative processes but also build public trust in the government.